2012
DOI: 10.1111/j.1440-1746.2012.07205.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical risk in patients with cirrhosis

Abstract: Surgery in the patient with cirrhosis is problematic, as encephalopathy, ascites, sepsis and bleeding are common in the postoperative period. Accurate preoperative assessment and planning, and careful postoperative management have the potential to reduce the frequency and severity of such complications, and reduce the length of hospital stay, but there is little literature evidence to prove this. Operative mortality and other risks correlate with the severity of the liver disease, co-morbidities and the type o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 37 publications
0
51
0
5
Order By: Relevance
“…From the clinical perception, cirrhotic patients would seem to be poor candidates for invasive procedures such as ESD because of concerns about increased procedure-related complications [11, 15]. However, several studies have reported the feasibility of gastric ESD for patients with liver cirrhosis, reporting post-procedural bleeding rates of 4.3–16.7 % and perforation rates of 0–1.5 % [16–20].…”
Section: Discussionmentioning
confidence: 99%
“…From the clinical perception, cirrhotic patients would seem to be poor candidates for invasive procedures such as ESD because of concerns about increased procedure-related complications [11, 15]. However, several studies have reported the feasibility of gastric ESD for patients with liver cirrhosis, reporting post-procedural bleeding rates of 4.3–16.7 % and perforation rates of 0–1.5 % [16–20].…”
Section: Discussionmentioning
confidence: 99%
“…Preoperatively, it is important to evaluate patients for liver disease since it has been associated with increased postoperative complications and mortality [52]. With the patient's history of hepatitis C, the next step was to assess the severity of liver dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperatively, it is important to evaluate patients for liver disease since it has been associated with increased postoperative complications and mortality [28]. With the patient's history of hepatitis C, the next step was to assess the severity of liver dysfunction.…”
Section: Discussionmentioning
confidence: 99%